Cannulation for Neonatal and Pediatric Extracorporeal Membrane Oxygenation for Cardiac Support - Harvey, Chris (Frontiers in Pediatrics, 2018)
The use of ECMO has increased over recent years providing respiratory and cardiac support. Optimal cannula placement is essential for succesful patient outcomes. Mutiple cannulation stratergies may be employed depending on the age/weight of the patient and their underlying condition. This article discusses cannulation technique focusing on the cannulation of paediatric and neonatal patients for cardiac support on ECMO.